Návrh marketingové strategie pro firmu - Rytina, Daniel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Diplomová práce se soustředí na návrh marketingové strategie pro nově vzniklou firmu WAXEXPERT s.r.o. zabývající se čistěním interiérů automobilů. Teoretická část práce pojednává o marketingu a marketingovém plánování. V praktické části, jsou zpracovány konkrétní návrhy marketingové strategie a prezentace firmy pro zákazníky.

This thesis focuses on the proposal of marketing strategy for the newly formed company WAXEXPERT s.r.o. engaged in cleaning car interiors. The theoretical part deals with marketing and marketing planning. In the practical part, are prepared concrete proposals marketing strategy and company presentations for customers.
Marketing Strategy Proposal for a Company
Keywords: Marketing; SWOT analýza; marketingový průzkum; Marketing; SWOT analysis; marketing research